The processes and problems involved in winding up a deceased estate in South Africa - Mazwi, Likho Athule (Rhodes University, Faculty of Commerce, Department of Accounting)
This thesis discusses the processes involved in winding up a deceased estate and potential problems that can occur in carrying out these processes. The research adopts a legal interpretive approach, more specifically a doctrinal research methodology. This is low risk desktop research and is based on publicly available data. In analysing the processes involved in winding up an estate, a will (or lack of a will) is identified as the starting point for the process. A will stipulates how the testator wishes to dispose of his or her property in the event of death, and must be executed in terms of the formalities provided in section 2 of the Wills Act. Section 13(1) of the Administration of Estates Act provides that the estate of the deceased is not wound up until letters of executorship have been granted by the Master. The Administration of Estates Act provides for formalities in the appointment and remuneration of an executor, who is responsible for the administration of the estate and distribution of the assets in the estate. Before the properties can be distributed to the beneficiaries, the executor must first call every person who has a claim against the estate to lodge a claim and pay the debts, including tax debts owed by the deceased. These tax liabilities are determined in terms of the Income Tax Act and Estate Duty Act. The three taxpayers involved in the winding-up process are the deceased taxpayer, the deceased estate, and the beneficiaries of the estate. Several problems that may occur in winding up an estate are identified in the thesis. These include a testator who is incapable of executing a will, wills that do not comply with the formalities, forged wills, undue influence exerted on a testator, the death of testator caused by a beneficiary, disqualified beneficiaries, lost wills, the lack of a valid will, disputed and late claims against the estate, an executor failing to perform his or her duties, removing the executor of an estate, winding up the estate of a person who has died without a will, and insolvent estates. These problems, together with possible solutions, are discussed in detail.
Keywords: Estates (Law); Wills; Testator; Executors and administrators; Income tax; Inheritance and transfer tax -- South Africa